Pyrolytic Carbon Films with Tunable Electronic Structure and Surface Functionality: A Planar Stand‐In for Electroanalysis of Energy‐Relevant Reactions. Issue 3 (16th January 2020) - Parker, Joseph F.; So, Christopher R.; Sassin, Megan B.; Ko, Jesse S.; Jeon, Seokmin; Chervin, Christopher N.; Lytle, Justin C.; Helms, Maya E.; Rolison, Debra R.; Long, Jeffrey W.
Abstract: Fundamental charge‐transfer dynamics for technologically relevant carbons, such as disordered "hard" carbons, can be studied by designing planar mimics. We fabricate thin films of "pyrolytic carbon" (pyC) by decomposition of benzene at 1000 °C and examine the physical and electrochemical properties of the native pyC film, as well as variants after heteroatom doping, plasma oxidation, and metal nanoparticle modification. The pyC films are optically reflective at the macroscale, relatively planar (1–3 nm RMS roughness by atomic force microscopy) and disordered (via Raman scattering). Thiophenyl‐doped pyC films (0.6–1.7 atom % sulfur) suitably mimic the disorder, chemical state (X‐ray photoelectron spectroscopy), and work function (Kelvin probe) of a workhorse carbon black, Vulcan XC‐72. Using ferri/ferrocyanide as a redox probe, we find that oxygen functionalities enhance the heterogeneous electron‐transfer rate constant up to 3×, while high levels of sulfur dopants decrease the rate 2×. We also explore thiophenyl‐directed adsorption of Au nanoparticles and show that hydrogen evolution at 0.1 mA cm −2 occurs ∼95 mV more positive at <1 % Au@pyC∼S than at pyC∼S. Abstract : A model substrate : We fabricate thin films of "pyrolytic carbon" (pyC) by decomposition of benzene at 1000 °C and examine the physical and electrochemical properties of the native pyC film, as well as variants after heteroatom doping, plasma oxidation, and metal nanoparticle modification.